FAMILY SUPPORT AS A SOURCE OF MENTAL RESILIENCE STRENGTH AMONG ISLAMIC GUIDANCE AND COUNSELING STUDENTS - Aina; Cut Metia (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Students are a group vulnerable to academic, social, and emotional pressures during the learning process in higher education. These conditions require strong mental resilience so that students can survive, adapt, and face various challenges in academic life. This study aims to analyze family support as a source of mental strength among students of the Islamic Guidance and Counseling Study Program at the State Islamic University of North Sumatra. This study employed a qualitative approach with a case study research design. The research informants consisted of six students selected through purposive sampling. Data were collected through in-depth interviews and analyzed using NVivo 12 Plus, with coding, categorization, and data visualization. The results showed that family support plays an important role in strengthening students’ mental resilience through emotional, instrumental, informational, and appraisal support. Such support helps students remain calm, confident, motivated, and capable of handling academic pressures and various challenges during their studies. Attention, motivation, financial assistance, advice, and appreciation from family become reinforcing factors that help students survive and adapt in higher education. This study concludes that family support is a primary factor in building and strengthening the mental resilience of Islamic Guidance and Counseling students throughout their academic journey.